PENERAPAN DIGESTER ANAEROBIK PORTABLE KAPASITAS 500 LITER DI GAPOKTAN SATO AMERTA UTAMA DESA BALUK - I.G.A.K. Suriadi; A.A.I.A.S. Komaladewi; T.G.T. Nindhia; I.K.A. Atmika; I.P.A. Astawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Livestock activities carried out by the Baluk village community with a minimum number of livestock in each family of 2 cows and pigs have the potential to develop new and renewable energy systems, in this case household-scale biogas energy. Thus each household can produce energy for their daily needs. Optimization and cost efficiency with the introduction and application of biogas/portable biogas digester technology by utilizing cow dung as a daily energy source is the focus of this service. A portable anaerobic digester was prepared in this work as a solution. Its capacity is around 500 liters making it suitable for household scale livestock manure processing. The material used for the digester is stainless steel 304. The digester is equipped with an agitator to optimize biogas production. Cow dung slurry (50% cow dung + 50% water) is used to feed the digester. There are 2 variations of the slurry loading speed carried out in this work, namely 5 liters/day slurry and 10 liters/day slurry. The biogas production rate is around 51.7 liters of biogas/day if filled with 5 liters/day of slurry. The biogas production rate was found to increase significantly to 82 liters of biogas/day if filled with 10 liters/day of slurry. So to overcome community problems and in carrying out solutions to village problems, several methods are used, including: counseling methods, mentoring methods, mutual cooperation methods, methods of applying appropriate technology, and pilot methods. The activities were carried out on August 23 2020 and September 18 2020. Keywords : Biogas, digester portable, optimation, 500 liter